Macrominerals in free-ranging Swedish reindeer during winter - Åhman, Birgitta; Rydbeg, Axel; Åhman, Gustaf (Rangifer, 1986)
Samples of blood, rumen, and caecal contents were taken from 238 reindeer (Rangifer tarandus) slaughtered between September and March in two consecutive years. Levels of magnesium, calcium and phosphorus were measured to evaluate the extent to which levels of these minerals reflected changes in the grazing conditions through the winter. Twenty-one reindeer in poor conditon were included in the investigation and compared with normal animals with respect to the investigated minerals. Serum values in September were within the normal range for domestic sheep (Ovis spp.) and cattle (Bos spp.) (Church, 1979). Magnesium was 0.9±0.1 mmol/l, calcium 2.8 ± 0.3 mmol/l and phosphorus 2.5 ± 0.5 mmol/l. Calcium values did not change very much through the winter while magnesium and phosphorus constantly decreased from September to February. Extremely low serum magnesium values (below 0.3 mmol/l in some animals where found in January and February. The majority of the animals in poor condition had low serum-magnesium values.